STRATEGI MENINGKATKAN QUALITY ASSURANCE PADA SATUAN PENGAWASAN INTERNAL PERUM JASA TIRTA II JATILUHUR: STRATEGY FOR IMPROVING QUALITY ASSURANCE ON THE INTERNAL AUDIT UNIT OF PERUM JASA TIRTA II JATILUHUR - Budi Hanta Prawiro; Dedi Budiman Hakim; Agus Maulana (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
This study aimed to formulate alternative strategies and determine priority strategies to improve internal audit quality assurance. This was a case study on Jasatirta II Internal Audit by evaluating the level of quality assurance in 2017. The analysis used was SWOT, EI, Fishbone and Analytic Network Process (ANP). The purposive judgment samples included Auditors, Board of Directors and Commissioners, Management, and Academics. The results showed that problems in quality assurance from 6 aspects of the Internal Auditor Capability Model (IA-CM) were: from roles and services aspects: less maximum audit service (53.10%) and other services (60%), from governance structure aspects: inadequate infrastructure (67.70%), from organization’s cultural relationship aspects: work culture fulfillment (51.70%), while aspects of HR management, professional practice, as well as performance management and accountability were still within reasonable limits (above 60%). The SWOT analysis in quadrant I and Matrix I/E in cell IV showed that the position of the organization grows, develops, and strong. Therefore, the fishbone diagram raised 3 alternative strategies to improve IA quality assurance: strengthening the Board of Directors and Commissioners, strengthening infrastructure through IT, and focusing on strengthening independent HR. Determination of the strategy chosen through ANP was the strengthening of support from BOD/BOC (40.98%). Keywords: ANP, fishbone analisys, internal audit, internal/extenal analisys, quality assurance, SWOT Analisys